2018
DOI: 10.1017/s0031182017002323
|View full text |Cite
|
Sign up to set email alerts
|

Ceratomyxa gracillima n. sp. (Cnidaria: Myxosporea) provides evidence of panmixia and ceratomyxid radiation in the Amazon basin

Abstract: We describe a new freshwater myxosporean species Ceratomyxa gracillima n. sp. from the gall bladder of the Amazonian catfish Brachyplatystoma rousseauxii; the first myxozoan recorded in this host. The new Ceratomyxa was described on the basis of its host, myxospore morphometry, ssrDNA and internal transcribed spacer region (ITS-1) sequences. Infected fish were sampled from geographically distant localities: the Tapajós River, Pará State, the Amazon River, Amapá State and the Solimões River, Amazonas State. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…This adaptation to a specific ecological niche may lead to high parasite gene flow over broad geographic areas. For instance, Zatti et al (2018) observed an absence of genetic variation in the typically more variable ITS-1 region in widely separated Ceratomyxa gracillima samples infecting the gall bladder of the Amazonian catfish Brachyplatystoma rousseauxii Castelnau, 1855. They suggest high gene flow as a result of panmixia in the parasite populations due to migratory behaviour of the fish host.…”
Section: Discussionmentioning
confidence: 99%
“…This adaptation to a specific ecological niche may lead to high parasite gene flow over broad geographic areas. For instance, Zatti et al (2018) observed an absence of genetic variation in the typically more variable ITS-1 region in widely separated Ceratomyxa gracillima samples infecting the gall bladder of the Amazonian catfish Brachyplatystoma rousseauxii Castelnau, 1855. They suggest high gene flow as a result of panmixia in the parasite populations due to migratory behaviour of the fish host.…”
Section: Discussionmentioning
confidence: 99%
“…These authors observed differences in the number of host species infected by a given species of myxosporean in a study conducted on species of the genus Cichla Schneider, 1801, which have differences in their distribution within the Amazon Basin. Similarly, Zatti et al (2018b) described the presence of Ceratomyxa gracillima Zatti, Atkinson, Maia, Bartholomew & Adriano, 2018 in populations of the Amazonian catfish Brachyplatystoma rousseauxii Castelnau, 1855 collected at localities of wide geographic separation and considered that this finding is a result of the exceptionally long-distance migration of this fish. In addition, Whipps & Kent (2006) suggested that host distribution and migration are important factors in maintaining parasite gene flow over broad geographic areas.…”
Section: Discussionmentioning
confidence: 95%
“…In this case, the ancestral Sphaerospora may have been introduced to the freshwater environment during marine incursions by its ancestral fish host, as observed in Ceratomyxa and monogenean parasites and their respective fish hosts, that is cichlids and Plagioscion spp. (Boeger & Kritsky, 2003;Friedman et al, 2013;Zatti et al, 2018), subsequently adapting to the freshwater conditions.…”
Section: Discussionmentioning
confidence: 99%